Respuesta :

Answer:x=4

Step-by-step explanation: ok this is pretty long but here we go

  1. you can 2x+6−3x=−2x+10
  2. Simplify  2x+6-3x2x+6−3x  to  -x+6−x+6
  3. −x+6=−2x+10
  4. Regroup your terms to give you 6−x=−2x+10
  5. Subtract 6 from both of your sides to give you −x=−2x+10−6
  6. Simplify  -2x+10-6−2x+10−6  to  -2x+4−2x+4 to give you −x=−2x+4
  7. Add 2x2x to both of your sides to give you −x+2x=4
  8. Simplify  -x+2x−x+2x  to  xx to give you you answer of x=4
  9. - answer x=4  Hope this helps

Otras preguntas